Propagation characteristics of femtosecond soliton and development of wavelength converter and analog-to-digital converter model - Esmaeilian-Marnani, Aida (2012)
Research interests on femtosecond solitons have increased along with upgrading in ultrafast optics. Moreover, all-optical devices have been developed based on ultrashort solitons. Despite the wide attraction of femtosecond solitons, which lies in providing high resolution, high intensity, and high bandwidth, attempt in this realm is associated with more complexity and more problems due to manifestation of higher order linear and nonlinear effects. To get around these obstacles, many researches have been conducted during the last decades in both, reducing the destructive effects on pulse propagation and developing optimal devices based on ultrashort solitons. This dissertation investigates the potential of overlapping 50 femtosecond soliton in improving the propagation characteristics as a low power ultrafast pulse over standard single-mode fiber (SSMF). Pulse stream propagation is also explored. Moreover, realization of two all-optical devices, ultrafast wavelength conversion,and two-bit analog-to-digital conversion, are investigated for ultrashort solitons. First, improving the 50 femtosecond pulse propagation is realized by substituting input pulse with a reduced-order overlapping soliton pair. This approach decreases the pulse time delay compared to fundamental soliton and increases the pulse stability compared to reduced-order soliton. In the pulse stream, in addition to using overlapping soliton pair, perturbation is also applied to the fiber by step change in the second order dispersion to avoid pulses from collision. Second, survey on the realization of wavelength conversion, which is based on second-order 50 femtosecond dark solitons with hyperbolic secant pulse, is accomplished by introducing localized dispersion perturbation along the optical fiber. It is shown that the realization of 1×2 channel wavelength converter for femtosecond pulses is possible. Ultimately, realization of two-bit all-optical analog-to-digital conversion is explored for analog signal sampled by a 50 femtosecond soliton sequence. Two methods are exploited. The first one is based on filtering the broadened soliton spectrum after evolution over half of the soliton period. In the second one, pulse is temporally sampled at the specified times after propagating through one soliton period. The utilized methods in this research have fast response and relatively simple design in comparison to the existing solutions. Consequently, the main contributions include research for improving femtosecond pulse and pulse stream propagation over short fiber lengths, realization of all-optical wavelength conversion for dark soliton with hyperbolic secant pulse, and two-bit alloptical analog to digital conversion for femtosecond soliton.